Starfish (Asteroidea, Echinodermata) from Iceland; spatial distribution and abundance. (October 2021) - Ringvold, H.; Guðmundsson, G.; Andersen, T.
Abstract: The Benthic Invertebrates of Icelandic Waters programme (BIOICE) was conducted between 1991 and 2004, for the purpose of gathering specimens within the Icelandic Exclusive Economic Zone (59° 58′N – 69° 35'N and 30° 52'W – 5° 34′W). In total 12961 asteroid specimens were collected from 654 sampling stations, which comprises 63% of all sampling stations. Sampling depths were between 20 and 2700 m. Total recorded asteroids for Iceland now include 64 species from 21 families and 45 genera, including 23 new species added from this study. The most abundant asteroids collected by BIOICE were Pontaster tenuispinus, Bathybiaster vexillifer and Henricia pertusa group. Maximum species richness was found at depths 100–200 m and 400–500 m, located above the cold Norwegian Sea Deep Water (−1 °C). 24 of the species were recorded at an abundance-weighted mean depth below 1300 m. The area south of the Greenland-Scotland Ridge (GS-Ridge) was more species rich than north of the ridge. Specimens within the rare Myxasteridae family were recorded. A nonmetric multidimensional scaling (NMDS) converged fast from multiple starting points with stress = 0.18. All five abiotic factors (depth, temperature, salinity, latitude and longitude) were strongly related to two of the NMDS ordination axis. The first ordination axis scores had strongest correlation with depth (r = 0.84), whereas the second ordination axis scores had strongest correlation with latitude (r = 0.71). Highlights: The BIOICE programme collected benthic fauna from within Icelandic EEZ, during 1991 and 2004. We provide an account of Asteroidea species from BIOICE, including NMDS analysis. A total of 64 asteroid species from 21 families and 45 genera are now recorded from Iceland. 23 new species were added from this study. Two NMDS axis are strongly related to depth, temperature, salinity, latitude and longitude.